Measuring anti-bunching Effect from Single Dye Molecules and Single Quantum Dots - Bao, Nguyen Thi Thanh; Trung, Dinh Van; Phuong, Dang Tuyet (Communications in Physics, 2016)
Antibunching is a quantum effect demonstrating clearly the quantum nature of the radiation field. Its detection through measurements of the second order correlation function is a direct proof of the presence of single molecule or single nano particle. In this paper we present the experimental setup of the Hanbury Brown - Twiss interferometer and the measurement results of the antibunching effect from single Rhodamine B dye molecules and single CdTe quantum dots in dilute solution. By fitting the second order correlation data, we derive a fluorescence lifetime of approximately 2 ns for Rhodamine B and 45 ns for CdTe quantum dots. Our results demonstrate an alternative way for determining the fluorescence lifetime using the antibunching effect